COMPETITION LAW AND POLICY FOR THE INTERNET OF THINGS - Nikolic, Igor (Pravni zapisi, 2022)
The Internet of Things (IoT) brings mobile internet connectivity to many differentsectors of the economy. 5G standard is expected to play a key role in fostering seamlessconnectivity between devices. However, it also requires licensing patents essential for 5Gstandards to a diverse group of companies. How to effectively license essential patents in IoThas been the central question in recent policy debates before the European Commission.Competition law has often been invoked as a solution to either directly regulate certainlicensing practices or to take a step back and enable the industry to collectively agree oncertain licensing solutions. The article analyses three situations where the role of competitionlaw was discussed: i) refusal to license patents to different levels of the production chain; ii)collective price-setting of a standard and iii) collective licensing of patents. The articleexamines each situation and discusses the appropriate role of competition law in fosteringefficient licensing of essential patents in the IoT.
Keywords: standard-essential patents; IoT; 5G; competition law